2009
DOI: 10.1200/jco.2009.22.0616
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Bevacizumab in Patients With Non–Small-Cell Lung Cancer and Brain Metastases

Abstract: Addition of bevacizumab to various chemotherapy agents or erlotinib in patients with NSCLC and treated brain metastases seems to be safe and is associated with a low incidence of CNS hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(143 citation statements)
references
References 19 publications
5
135
0
3
Order By: Relevance
“…In this respect, the safety of the combination of chemotherapy with Bev and brain radiotherapy has been previously documented in patients with non-SCLC. 32 In the recent Safety Evaluation of a Combination of Brain Radiation Therapy and Bevacizumab for Treatment of Brain Metastasis (REBECA) phase I trial Bev was evaluated in combination with WBRT in patients with brain metastases from solid tumors and achieved some encouraging results, which suggested a potential synergistic effect between Bev and radiation therapy. 33 In this regard, it should be also noted that the bloodebrain barrier is disrupted during brain radiotherapy, hence, the penetration of chemotherapy drugs and Bev through it might be facilitated.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the safety of the combination of chemotherapy with Bev and brain radiotherapy has been previously documented in patients with non-SCLC. 32 In the recent Safety Evaluation of a Combination of Brain Radiation Therapy and Bevacizumab for Treatment of Brain Metastasis (REBECA) phase I trial Bev was evaluated in combination with WBRT in patients with brain metastases from solid tumors and achieved some encouraging results, which suggested a potential synergistic effect between Bev and radiation therapy. 33 In this regard, it should be also noted that the bloodebrain barrier is disrupted during brain radiotherapy, hence, the penetration of chemotherapy drugs and Bev through it might be facilitated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with brain metastases were excluded from both trials due to concerns that bevacizumab may increase the risk of intracranial hemorrhage. The safety of bevacizumab in patients with treated brain metastases was subsequently established by the PASSPORT trial [Socinski et al 2009] and generally manageable toxicity of bevacizumab was confirmed in the SAIL study, an open-label phase IV study, which did not reveal any new safety signals [Crino et al 2010].…”
Section: Vegfmentioning
confidence: 99%
“…Among 743 patients included in the final analyses, 29 presented BM at baseline. A pooled analyses (33) of the 131 patients with treated BM receiving bevacizumab in either PASSPORT (28) or ATLAS (29) reported no symptomatic grade >2 brain haemorrhage during the main treatment phases of study. In the ATLAS trial one grade 2 CNS haemorrhage occurred during treatment after CNS progression (29).…”
Section: Angiogenesis In Brain Metastasesmentioning
confidence: 99%
“…Bevacizumab safety was first investigated in patients with asymptomatic treated BM. Five prospective trials, PASSPORT, ATLAS, BeTa, ERACLE and PRONOUNCE trials included patients with treated BM and recorded a low rate of CNS haemorrhage (28)(29)(30)(31)(32).…”
Section: Angiogenesis In Brain Metastasesmentioning
confidence: 99%